Impact of climate change on irrigation, crops and hydropower in Vietnam - Yohannes Gebretsadik; Charles Fant; Kenneth Strzepek (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Vietnam is among the countries that are assumed to be highly affected by the impacts of climate change through sea level rise; increased temperature and changes in precipitation resulting in changes in crop water requirements and yields; and changes in river flow with impacts on hydropower and the ability to meeting water requirements for municipal, industrial and agricultural uses. Fifty-six climate change scenarios for Vietnam were selected that span a range of wet to dry future climates for Vietnam. A set of biophysical models were employed to project the impacts on water supply, water demand and hydropower generation out to the year 2050. These climate scenarios show a drying trend in the north with an increase of precipitation in the central and southern regions. Model results suggest that dry season runoff will generally be reduced and that wet season peak runoff will be increased compared to current conditions with mean annual runoff, with extreme climate scenarios indicating increases up to 20 percent and decreases to 16 percent. Crop modeling results suggest that irrigation demand will mostly increase over Vietnam. The integrated river basin analysis over the 22 basins of Vietnam shows that overall hydropower generating capacity is typically only mildly affected by 2041 to 2050.
Keywords: Q54; 330; climate change; water systems; agriculture; hydropower; Vietnam; Klimawandel; Bewässerung; Ernte; Wasserkraft; Vietnam